2023
DOI: 10.1186/s12877-023-04241-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of social frailty and its associated factors in the older Chinese population: a national cross-sectional study

Xin Qi,
Yingying Li,
Jiabin Hu
et al.

Abstract: Background Social frailty has not been comprehensively studied in China. Our objective is to investigate the prevalence of social frailty among the older population in China, as well as identify relevant factors and urban-rural differences. Methods We obtained data from the Fourth Sample Survey of the Aged Population in Urban and Rural China (SSAPUR) database. The study employed a multistage, stratified, cluster-sampling method, recruiting a total … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The Aira/Isa and Soo areas are also populous and considered urban areas. A previous study indicated that urban-rural residential differences are signi cantly associated with social frailty [22] . Meanwhile, it is also revealed that residential disparities are identi ed in the linkage of oral health knowledge and practices with frailty [23] .…”
Section: Discussionmentioning
confidence: 98%
“…The Aira/Isa and Soo areas are also populous and considered urban areas. A previous study indicated that urban-rural residential differences are signi cantly associated with social frailty [22] . Meanwhile, it is also revealed that residential disparities are identi ed in the linkage of oral health knowledge and practices with frailty [23] .…”
Section: Discussionmentioning
confidence: 98%
“…The narrative review shows that aging is one of the critical risks for frailty syndrome [10][11][12]. As age increases, vulnerability to conditions associated with aging, such as frailty syndrome, becomes more prevalent.…”
Section: Agingmentioning
confidence: 99%
“…The narrative review shows that living in rural contexts is another critical risk for frailty syndrome [10][11][12].…”
Section: Rural Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…In today's healthcare systems, the increasing number of older patients presents a significant challenge [ 1 ]. This shift toward an aging society places substantial demands on healthcare facilities and resources [ 2 ].…”
Section: Introductionmentioning
confidence: 99%